Boxing-related maxillofacial and orbital trauma: a retrospective NEISS database analysis of injury patterns and emergency diagnostic prioritization (2014–2023) - Daniel Lynch; Lorenzo Petralia; John Komlos; Troy Puetz; Sarah Peterson; Steiv Shore; Benjamin Tinker; Michael N. Megafu (Journal of Emergency and Disaster Medicine, 2026)
Abstract Introduction/background Using the National Electronic Injury Surveillance System (NEISS) database, this study analyzes boxing-related maxillofacial and orbital injuries presenting to emergency departments nationwide, identifying injury patterns to better equip clinicians for accurate diagnosis and optimized patient outcomes. Objective(s) To characterize the distribution of boxing-related maxillofacial injuries requiring hospitalization from 2014 to 2023 and to establish evidence-based diagnostic and management priorities for emergency physicians, ophthalmologists, and surgeons. Methods — design Retrospective national database analysis. IRB approval was not required as only publicly available data were utilized. Setting Statistically representative sample of U.S. hospital emergency departments via the NEISS database. Participants Patients presenting to emergency departments with boxing-related head and neck injuries (eye, head, face, mouth, ear) from 2014 to 2023 ( n = 1,012 maxillofacial hospitalizations from 37,203 total national admissions). Excluded: extremity/torso injuries; burns, toxicology, amputation, electroshock, or submersion. Interventions Not applicable (observational/database study). Main outcome measures Annual incidence of boxing-related maxillofacial injuries, anatomical distribution of injury location, frequency of specific diagnoses at hospitalization, and burden index (maxillofacial injuries per 1,000 boxing ER admissions). Results Analysis of NEISS data from 2014 to 2023 identified 1,012 maxillofacial hospitalizations from 37,203 total boxing-related emergency admissions (overall rate 2.7%). In the corrected case-level cohort ( n = 21), mandibular fractures (33.3%) and orbital floor blowout fractures (28.6%) were the predominant maxillofacial diagnoses, collectively representing 61.9% of cases. Associated intracranial diagnoses comprised concussion/CHI (14.3%) and subdural hematoma (9.5%); nasal injury accounted for 9.5% and other facial fracture 4.8%. Head (43.0%) and face (37.3%) together accounted for > 80% of all admissions. A strong positive Pearson correlation was identified between ER admissions and maxillofacial injuries ( r = 0.893, p = 0.0005). Diagnosis distribution was significantly non-uniform (χ² = 139.1, p < 0.001). The cohort was 95.2% male with a median age of 19 years. Conclusion These findings provide population-specific epidemiological evidence supporting the application of existing validated imaging protocols to boxing-related maxillofacial trauma. The predominance of mandibular and orbital floor fractures (61.9%) is consistent with the Wisconsin Criteria clinical examination triggers and supports consideration of concurrent CT maxillofacial with fine-cut orbital views and CT head without IV contrast for hemodynamically stable patients when clinical examination findings meet established imaging criteria, per ACR Appropriateness Criteria. When neurological compromise requires prioritization, urgent non-contrast CT head should be obtained first, followed by maxillofacial CT as clinical status permits. Recognizing these patterns enables faster, more accurate management of ophthalmic and maxillofacial injuries, reducing morbidity and improving outcomes.